2015
DOI: 10.1002/jor.23048
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical benefits of anterior offsetting of humeral head component in posteriorly unstable total shoulder arthroplasty: A cadaveric study

Abstract: Restoration of joint stability during total shoulder arthroplasty can be challenging in the face of severe glenoid retroversion. A novel technique of humeral head component anterior-offsetting has been proposed to address posterior instability. We evaluated the biomechanical benefits of this technique in cadaveric specimens. Total shoulder arthroplasty was performed in 14 cadaveric shoulders from 7 donors. Complementary shoulders were assigned to either 10˚or 20˚glenoid retroversion, with retroversion created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Recent biomechanical data have demonstrated increased resistance to posterior humeral head translation and improved joint contact pressures in shoulders with significant glenoid retroversion treated with an anterior-offset technique. 11 Finite element analysis has confirmed an anterior shift in the center of pressure with an anterior-offset humeral head in the setting of increased glenoid retroversion. 12 Hsu et al 9 have reported good outcomes for a series of 33 patients undergoing either total shoulder arthroplasty or hemiarthroplasty who required an anterior-offset humeral head technique to correct intraoperative posterior humeral head subluxation.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Recent biomechanical data have demonstrated increased resistance to posterior humeral head translation and improved joint contact pressures in shoulders with significant glenoid retroversion treated with an anterior-offset technique. 11 Finite element analysis has confirmed an anterior shift in the center of pressure with an anterior-offset humeral head in the setting of increased glenoid retroversion. 12 Hsu et al 9 have reported good outcomes for a series of 33 patients undergoing either total shoulder arthroplasty or hemiarthroplasty who required an anterior-offset humeral head technique to correct intraoperative posterior humeral head subluxation.…”
Section: Discussionmentioning
confidence: 89%
“… 14 Over time, the soft tissues about the shoulder adapt to the posterior position of the proximal humerus, and these forces can be difficult to overcome with corrective reaming or augmented components that realign the humerus anteriorly. In fact, Kim et al 11 postulated that correcting the humeral position may escalate the posterior pull of the soft tissues. Anteriorly offsetting the humeral head allows the head center to have congruent alignment to the glenoid center while allowing the proximal humerus to remain in a relatively posterior position, thus mitigating the adaptive posterior pull of the soft tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimens were randomly assigned to two groups; the control group (n ¼ 3) was comprised of specimens with no perforation of the glenoid, while the perforation group (n ¼ 7) was comprised of specimens with glenoid perforation. In the perforation group, we simulated an arthritic glenoid by eccentrically reaming the posterior glenoid more than the anterior glenoid to create approximately 15 of retroversion as described previously by Kim et al 9 In both groups, each specimen was prepared for routine TSA by the attending surgeon according to the standard surgical technique utilizing a deltopectoral approach. The humeral head was resected at the level of the anatomic neck, but no humeral component was implanted.…”
Section: Cadaveric Specimen Preparationmentioning
confidence: 99%
“…Biomechanical studies show that dialing the humeral head eccentricity anteriorly may reduce posterior eccentric loading and increase the force required to posteriorly dislocate the shoulder. 34 Theoretically, anterior overhang of the humeral head may potentially increase pressure on the subscapularis repair, although this has not been reported as a cause for subscapularis failure postoperatively. 35 Bone grafting of the posterior glenoid allows for glenoid version correction and decreased edge loading at the implant-bone interface, while enhancing bone stock.…”
Section: Goals Of Implant Placementmentioning
confidence: 99%